Using logarithms property of log(x)+log(y)=log(xy) so here, you can sum the equation to; [tex]log((x+6)*(x-6))=2[/tex] so you can simply say that; [tex] log_{8}((x+6)( x-6))=2 [/tex] and by multiplying (x+6)*(x-6) [tex]log_{8}(x^2-36)=2[/tex] and as you know also that; [tex] a^{b}=c [/tex] is same as [tex]log _{a}c=b [/tex] so you can simply state it as; [tex]8^2=x^2-36
64=x^2-36
64+36=x^2
x^2=100
x=10[/tex] And you can check your work by substituting with 10 instead of x in the original function. Hope this helps!